Ganoderma lucidum Polysaccharide Peptide Reduce Inflammation and Oxidative Stress in Patient with Atrial Fibrillation - Ardian Rizal; Ferry Sandra; Muhamad Rizki Fadlan; Djanggan Sargowo (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Atrial fibrillation (AF) could be triggered by inflammation and oxidative stress. Ganoderma lucidum has an active substance in the form of β-glucan that can reduce inflammatory process and oxidative stress in rats. The objective of this study was to evaluate the effect of Ganoderma lucidum polysaccharide peptide (GLPP) in paroxysmal AF subjects with parameters of anti-inflammatory antioxidant, electrocardiography and health-related quality of life (HRQoL).METHODS: A randomized closed-label clinical trial with pre- and post-test design was conducted. After AF subjects selection, the subjects were randomized, interviewed and veni-punctured to isolate blood plasma. AF Subjects were then treated with placebo or GLPP for 90 days. Post-test blood plasma was collected on the following day after the 90th day. Then anti-inflammatory and antioxidant parameters were measured. After that, echocardiographic and HRQoL assessments were performed.RESULTS: A total of 38 subjects, 11 males and 27 females, completed the study with no significant changes in diets, physical activities, or medications. Comparing to control, the 90-days GLPP-treated subject characteristics were significant difference in systolic blood pressure, heart rate, malondialdehyde, high-sensitivity C-reactive protein, tumor necrosis factor-a, interleukin (IL)-1b, IL-6, primary (P)-wave dispersion, P-max, physical functioning, limitation to physical health, energy/fatigue, pain, and physical limitation.CONCLUSION: GLPP has several potential effects in AF subjects, including anti-inflammatory, antioxidant, and atrial remodelling, so that HRQoL of AF subjects could be improved. Hence, GLPP could suggested as a potential supplementing agent for AF management.KEYWORDS: atrial fibrillation, Ganoderma lucidum, inflammation, antioxidant, atrial remodelling, quality of life